Toward a Pragmatic Conception of Metaphor - Youssef, Charbati (2001)
Much research has discussed metaphor from different angles and through the centuries, rhetoricians have enriched the study of metaphor by focusing on its various aspects. Rhetoricians' conceptions of metaphor have been always developed along various lines. They can be mainly classified into two general categories: the traditional conceptions and the new ones. The purpose of the present study was to trace the development of the conception of metaphor from the classical point of view to the modem one. The proper comprehension of metaphor cannot be realised without the knowledge of the development of the conceptions of metaphor. Therefore, this study aimed to complement other studies related to metaphor by placing the whole line of its development in perspective. The study found out that there are two main conceptions in the literature of metaphor: The classical conception and the modem one. The classical conception views metaphor as a play with words, an unnecessary use of language that causes misunderstanding while the modern conception views metaphor as a tool to investigate our comprehension of things. This study claims that the development in the conception of metaphor from the classical point of view to the modem has been a result of two observations that modem rhetoricians have noticed. The first observation is that metaphor is pervasive in our language and the second is that metaphor is related to our thinking and our conceptual system. In addition to this, the present study advocates a pragmatic conception of metaphor, that is, as a tool with which we can develop research in many scientific disciplines. The present study has proposed new domains in which the study of metaphor could benefit the researchers. The study focused on selected disciplines mainly psychology, sociology, and political science. However, other disciplines can also make use of metaphor and those need to be investigated based on the pragmatic conception of metaphor.